Role of genetics, environment, and their interactions in the pathogenesis of eosinophilic esophagitis. (October 2019) - Lyles, John; Rothenberg, Marc
Highlights: FLG, DSG1, CAPN14, SPINK5, and SPINK7 elicit esophageal epithelial barrier dysfunction. CCL26, POSTN, and TSLP link to Th2-mediated immunity. Environmental factors likely lead to esophageal microbial dysbiosis. BPA/phthalates, advanced glycation end products, and ingested nickel could be modifiable risk factors for developing EoE. Epigenetic modification identified in patients with EoE unresponsive to steroid treatment. Abstract : The rise in incidence and prevalence of eosinophilic esophagitis (EoE) since the 1990s has prompted investigations into its pathogenesis, natural history, and management. Identified genetic variants in FLG, DSG1, CAPN14, SPINK5, and SPINK7 link EoE to epithelial barrier dysfunction, whereas variants in CCL26, POSTN, and TSLP associate EoE with T helper type 2-mediated immunity. Early-life, infectious, and geographic factors have been implicated in promoting esophageal microbial dysbiosis and, subsequently, T helper type 2 immune responses. However, research into environmental factors and their interactions with genetic variants are not as developed as their genetic counterparts. Further research into the subgroups and epigenetics of EoE will likely promote further understanding.